Revision of fossil Bibionidae (Insecta: Diptera) from the Miocene of Radoboj, Croatia - Skartveit, John; Krizmanić, Katarina (Zootaxa, 2020)
We revise the available material of fossil bibionid flies from Radoboj, Croatia, and redescribe the species of which we have been able to locate material. We have found material of the following species: Penthetria anthracina (Heer, 1849), Penthetria cimicoides (Heer, 1849), Penthetria gracilis (Unger, 1841), Penthetria longa (Heer, 1849), Penthetria murchisonii (Unger, 1841), Plecia lugubris Heer, 1849, Plecia lygaeoides (Heer, 1849), Bibio crassinervis Skartveit & Pika, 2014, Bibio enterodelus Unger, 1841, Bibio firmus Heer, 1849, Bibio giganteus Unger, 1841 and Dilophus pinguis (Heer, 1849). Two species are shared with the approximately contemporary site of Öhningen, Southern Germany. Plecia bucklandi Heer, 1849 and Plecia morio (Heer, 1849) were recorded both from the Oligocene site of Aix-en-Provence, France and from Radoboj in the original descriptions, however we did not find any specimens from Radoboj conforming with the types from Aix-en-Provence.